Pro SMS 2003 - Kruetzfeld, Rod (Apress, 2012)
Systems Management Server (SMS) is Microsoft’s change and configuration management solution. It allows network administrators to provide software, updates, and remote connectivity quickly and cost-effectively from a central location. SMS 2003, the fifth revision of Microsoft’s product, offers additional features, such as asset inventory and management, remote diagnosis and troubleshooting, and operating system deployment (using the SMS Operating System Deployment Feature Pack).